Ontological study of problems in designing social science learning based on a Merdeka curriculum: A pilot study of social studies teachers in Malang city - Mufid, M. Khoirul Annas Waladul; Suprijono, Agus (Universitas Negeri Malang, 2024)
The change in the curriculum to the Merdeka Curriculum also changed the educational paradigm in Indonesia. Curriculum changes bring changes to the content of social studies learning, especially at the junior high school level, thus creating problems for teachers in designing social studies learning. This research aims to determine teachers' problems in designing learning from the perspective of ontological studies (learning content) due to curriculum changes. For this reason, a qualitative approach was used with a pilot study design to examine this matter. Data collection was carried out through document review and interviews. Meanwhile, data analysis is carried out using an interactive model. The results of this research indicate that changes in the curriculum have caused a lack of synchronization between content standards and expected achievements in social studies learning. This has implications for teachers' problems determining learning material at each grade level. Teachers also need clarification on the suitability of the learning content and what is expected from the curriculum. Not only that, but planning differentiated learning is also one of the problems in designing social studies learning materials. This research's limitation is that it is a pilot study and discusses a narrow scope, namely an ontological study. In future research, it is hoped that more in-depth research can be carried out on teacher problems from an epistemological and axiological perspective. So, the entire teacher's problems in designing social studies learning can be described.